The Data Dictionary – A Controlled Vocabulary for Integrating Clinical Databases and Medical Knowledge Bases - Linnarsson, R.; Wigertz, O. (Methods of Information in Medicine, 1989)
The medical information systems of the future will probably include the entire medical record as well as a knowledge base, providing decision support for the physician during patient care. Data dictionaries will play an important role in integrating the medical knowledge bases with the clinical databases.This article presents an infological data model of such an integrated medical information system. Medical events, medical terms, and medical facts are the basic concepts that constitute the model. To allow the transfer of information and knowledge between systems, the data dictionary should be organized with regard to several common classification schemes of medical nomenclature.
Keywords: Data Dictionary; Data Model; Medical Record; Terminology; Knowledge Base